Assessment of Fish Biodiversity of the Cimandiri Watershed, West Java, Indonesia - Gustiano, Rudhy; Haryono, Haryono; Wahyudewantoro, Gema; Krismono, Krismono; Rusdianto, Rusdianto; Nur, Firman M. (Makara Journal of Science, 2025)
Information on the fish biodiversity of the Cimandiri Watershed is incomplete, and human activities and anthropogen-ic impacts pose a significant threat to this biodiversity. The purpose of this study was to assess the biodiversity of fish in the Cimandiri Watershed. The results indicated that fish biodiversity in the area included 104 species belonging to 49 families. There were 26 species in the upstream area, 47 species in the middle area, and 61 species in the downstream area. Forty-three species were native to Indonesia, and 7 of the native fish were endemic to the area. There were 11 introduced species belonging to 6 families. Analysis of biodiversity status shows that 4 species were threatened, 2 spe-cies were near-threatened, 76 species were less considered, and 18 species have not yet been evaluated. Among the economically important species present, the eel is the most common in the Cimandiri Watershed. This study has re-vealed the profile of the Cimandiri Watershed, the characteristics of its ecosystem, fish biodiversity, economically im-portant fish species, the conservation status of fish species, and the threats to the fish biodiversity within it.